APPLICATION OF THE EARNED VALUE METHOD ON ROAD IMPROVEMENT PROJECTS IN NIAS SELATAN DISTRICT: PENERAPAN METODE EARNED VALUE PADA PROYEK PENINGKATAN JALAN DI KABUPATEN NIAS SELATAN - Laia, Sederhana (UPMI Proceeding Series, 2024)
Construction projects are growing rapidly over time. Each project has certain characteristics and requirements at each stage of project implementation in order to distinguish one project from another. The role of the owner, consultant and contractor is needed in project implementation to achieve maximum results. The cost and time control process is an important factor for the success and efficiency of project work. This study uses the Earned value method with a document study data collection method where the type of research uses quantitative with descriptive analysis. Data processing uses Microsoft Excel. The results of the study showed the SPI value from week 1 - week 11 of 0.59, in weeks 12 - 20 the SPI value was 2.97. The CPI value from week 1 - week 27 was 0.90 which means more wasteful costs. Estimated At Completion (EAC) using the Earned value method is IDR 20,298,475,550.24 with a projected loss of IDR 8,759,432,242.03. Estimated All Schedule (EAS) using the earned value method is 176 days.